lpsilateral Glaucoma in Sturge-Weber Syndrome - Mousa, G.Y.; Cullen, A.P (Canadian Journal of Optometry, 2021)
A case of Sturge-Weber syndrome in a young Chinese woman is presented. The classic facial cutaneous angioma extends to involve other parts of her body. lpsilateral glaucoma previously undiagnosed was detected. Associated field defects include enlargement of the blind spot and a general depression of the field.